Can 'too much' trust slow tourism development? An exploratory cross-country analysis. Issue 13 (3rd July 2021) - Kim, Young-Rae; Yap, Ghialy; Vertinsky, Ilan
ABSTRACT: This paper investigates a relationship between countries' trust and tourism development using data drawn from the World Value Survey. We hypothesize that social trust creates a positive influence on tourism development. However, this paper finds that, beyond a certain level of average social trust, more trust may have a negative impact on tourism development. We suggest that in-depth analysis is required to examine how social trust can promote or restrain tourism growth and identify the types of government policies that can nurture the relationships between trust and tourism development in positive directions.